2015
DOI: 10.1007/s11051-015-3093-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pure and copper (Cu)-doped ZnO nanorods for antibacterial and photocatalytic applications with their mechanism of action

Abstract: The present study reports the synthesis of pure and Cu-doped ZnO nanorods for antibacterial and photocatalytic applications. The samples were synthesized by simple, low cost mechanical-assisted thermal decomposition process. The synthesized materials were characterized by scanning electron microscopy, UV-Visible spectroscopy, and photoluminescence studies. The antibacterial activity of characterized samples was determined against Gram-positive bacteria such as Staphylococcus aureus and Streptococcus pyogenes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 34 publications
5
31
0
Order By: Relevance
“…Absorption bands at 376 and 510 nm could be seen for ZnO and CsPbBr 3 perovskite NPs, respectively. Compared to ZnO NPs, the higher red shift in the adsorption band of CsPbBr 3 perovskite NPs indicated that a higher percentage of solar light can be used for electron-hole pair generation [15] which is substantial in antibacterial activity. Moreover, the optical band gaps of ZnO and CsPbBr 3 perovskite NPs were calculated using Tauc's equation, by plotting (αhυ) 2 versus hυ [16], as depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Absorption bands at 376 and 510 nm could be seen for ZnO and CsPbBr 3 perovskite NPs, respectively. Compared to ZnO NPs, the higher red shift in the adsorption band of CsPbBr 3 perovskite NPs indicated that a higher percentage of solar light can be used for electron-hole pair generation [15] which is substantial in antibacterial activity. Moreover, the optical band gaps of ZnO and CsPbBr 3 perovskite NPs were calculated using Tauc's equation, by plotting (αhυ) 2 versus hυ [16], as depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…On boiling in water, the dark blackish red anthocynanins pigment oozed out as supernatant [ Figure 5]. to obtain four ZnO nanopowders with different aspect ratios [16] [17]. The obtained powders were then washed twice with distilled water, followed by drying in an oven at 80˚C for 8 hours.…”
Section: Zinc Nanomaterialsmentioning
confidence: 99%
“…Antibacterial mechanism of action of copper could be originated from creating active oxygen species and disrupting bacterial cells' membrane processes [9,10]. Modification of ZnO nanoparticles by Cu ions can improve the antibacterial property of resultant nanohybrids [11]. Moreover, the presence of ZnO nanoparticles in polymer coatings matrix could noticeably increase the produced coatings mechanical properties [12,13].…”
Section: Introductionmentioning
confidence: 99%